Study of the effect of WO3 and Bi2O3 on the microstructure and electrical properties of a TiO2 based varistor - Kothandapani Z.; Begum S.; Ahmad I.; Daud I.R.; Gholizadeh S. (Universiti Malaysia Pahang, 2023)
Titanium dioxide (TiO2) varistors doped with tungsten oxide (WO3) and bismuth oxide (Bi2O3) were investigated. The microstructure and electrical characterization were studied, where the effects of different concentrations of WO3 and a fixed amount of Bi2O3 were investigated. TiO2 based varistors have promising potential for the high performance development. The percentage of dopant was varied at various levels and the prepared samples were then characterized by evaluating IV relationships to determine the degree of non-linearity in the varistor. Evaluation was conducted based on non-linear coefficients, breakdown voltage and power loss. Microstructure analysis was also carried out using SEM. The average grain size was determined to find the relationship between microstructure and electrical properties. It was found that a molar concentration with 99.1%TiO2. 0.4%WO3. 0.5%Bi2O3 yielded the best results in terms of electrical and microstructural properties. The addition of 0.5%Bi2O3 and 0.4%WO3 creates a relatively low clamping efficiency, higher non-linear coefficient, low breakdown voltage and less power loss. © Universiti Malaysia Pahang, Malaysia.